Applying the Principles of Maqasid Al-Shariah to Address Poverty and Hunger in Indonesia - Fathoni Nur Alami; Wily Mohammad (Yayasan Adra Karima Hubbi, 2024)
This article synthesizes qualitative evidence from 25 academic papers that examine the integration of Maqasid Al-Syariah principles with efforts to achieve SDG 1 (eradication of poverty) and SDG 2 (food security) in Indonesia. In the context of the complexity of challenges such as conflict, climate change and the impact of the COVID-19 pandemic, this approach offers a unique perspective based on sustainable ethical and Islamic values. This article looks at the contribution of Maqasid Al-Syariah in improving food security and sustainable agriculture, as well as Indonesia's strategy to deal with the problem of hunger. Emphasizing values such as compassion, fair distribution and responsible management, this approach not only strengthens efforts to achieve SDG 1 and SDG 2, but also shows how Islamic principles can be applied through initiatives such as the Islamic Food Bank to reduce poverty and food insecurity in Indonesia .